Transcriptome Profiling of Transposon-Derived Long Non-coding RNAs Response to Hormone in Strawberry Fruit Development - Chen, Xi; Wang, Chengdong; He, Bing; Wan, Zifan; Zhao, Yukun; Hu, Fengqin; Lv, Yuanda (Frontiers in Plant Science, 2022)
Strawberry is an economic horticulture crop for fruit consumption. The ripening of its fruit is a complex biological process regulated by various hormones. ABA is a critical phytohormone involved in fruit ripening. However, little is known about the long non-coding RNAs (LncRNAs), especially transposon-derived LncRNA (TE-lncRNA), response to hormones during fruit ripening in octoploid strawberry. In the study, the transcriptome data of developing strawberry fruits treated with ABA and its inhibitor NGDA (Nordihydroguaiaretic acid) were analyzed to identify responsive LncRNAs and coding genes. A total of 14,552 LncRNAs were identified, including 8,617 transposon-derived LncRNAs (TE-LncRNAs), 412 LncRNAs (282 TE-LncRNAs), and 382 ABA-sensitive LncRNAs (231 TE-LncRNAs). Additionally, a weighted co-expression network analysis constructed 27 modules containing coding RNAs and LncRNAs. Seven modules, including “MEdarkorange” and “MElightyellow” were significantly correlated with ABA/NDGA treatments, resulting in 247 hub genes, including 21 transcription factors and 22 LncRNAs (15 TE-LncRNAs). Gene ontology enrichment analysis further revealed that ABA/NDGA-responsive modules, including LncRNAs, were associated with various metabolic pathways involved in strawberry fruit development and ripening, including lipid metabolism, organic acid metabolism, and phenylpropanoid metabolism. The current study identifies many high-confidence LncRNAs in strawberry, with a percentage of them being ABA pathway-specific and 22 hub-responsive LncRNAs, providing new insight into strawberry or other Rosaceae crop fruit ripening.